Breast cancer incidence and mortality before and after implementation of the German mammography screening program. Issue 3 (4th December 2019) - Katalinic, Alexander; Eisemann, Nora; Kraywinkel, Klaus; Noftz, Maria R.; Hübner, Joachim
Abstract : Effective population‐based mammography screening should impact breast cancer (BC) incidence, age and stage‐specific incidence and BC mortality. We aim to investigate such effects in a time period of 10 years after implementation of the German mammography screening program. Data on 323, 719 breast cancer patients from 2003 to 2014 for defined regions covering a population of 30 million inhabitants and official mortality data from 1998 to 2016 for almost the whole of Germany were used. We compared incidence and mortality rates for the prescreening time period (2003/2004) and the latest available data (2013/2014 and 2015/2016, respectively) and performed trend analyses using joinpoint regression models. In the screening exposed age groups (50–59 and 60–69 years), BC incidence showed a typical prevalence peak with the introduction of the mammography screening, mainly driven by an increase of early‐stage BC. For Stage III and IV BC incidence in 2013/2014 was 24.2 and 23.0% (age group 50–59 years) and 28.3 and 24.2% (age group 60–69 years) lower than in the prescreening period. From 2003/2004 to 2015/2016 BC mortality decreased by 25.8 and 21.2%, respectively. As corresponding trends in nonexposed age groups were distinctly unfavorable, the reduction of late‐stage BC incidence and BC mortality in the screening exposed age groups in Germany is most likely to be attributed to the introduction of the national mammography screening program. These positive effects are bought at the cost of a moderate occurrence of overdiagnosis, especially by a sharp increase of in situ cancers. Abstract : What's new? Effective mammography screening should have an impact on breast cancer (BC) incidence and mortality. Until today, however, there is little information available on the population‐based outcomes of the national breast cancer screening program in Germany. Here, the authors present age‐specific population‐based data before and after implementation of the program. Compared to non‐exposed age groups, screening‐eligible women showed more favorable trends regarding the incidence of late‐stage BC and BC mortality. A persistent excess of BC incidence, mainly driven by an increase of in situ cancers, indicated a moderate amount of overdiagnosis.